PEMBANGUNAN SISTEM INFORMASI PEGAWAI NEGERI SIPIL DI RSUD SURAKARTA BERBASIS WEB RESPONSIF - Siti Muslikhah Anjarwani; Hardika Khusnuliawati (JURNAL GAUNG INFORMATIKA, 2018)
RSUD Surakarta is a government institution that is engaged in health sector as a regional general hospital. Previously, RSUD Surakarta already have an applicationsystem such as Inpatient System and Outpatient System. RSUD Surakarta also has a centralized system from the Government of Surakarta City that is AttendanceSystem.However RSUD Surakarta is still a new institution, therefore many application systems are still run manually. One of them is Civil Servant Information System. Forinformation problems, should always keep pace with the latest technological developments. The presentation of interesting information is needed to capture theinterest of the public in obtaining information. especially regarding the issue in question. The research method used is observation, interview, and documentation method. Analyst tools used are DFD, Flowchart System, Flowchart Program and ContextDiagram. The result of this research is a web-based civil service information system located in RSUD Surakarta as processing and controlling employee data andinformation media.